Geographical Indications in Trade Commodities for Promoting Sustainable Economic Development in Indonesia - Dwi Tiara Kurnilasari (University of Jember, 2020)
The recent COVID-19 pandemic has disrupted many countries. It leads them to imbalance conditions in various sectors, particularly in the economic sector due to the shifting of people's habits. Amidst the recession, Indonesian local horticulture commodities increase in rates, supporting Indonesia's revenue. In Indonesia, abundant natural resources with numerous potential Geographical Indications (GI) need the government and other related parties' intense role. It currently results in weakness in many ways to support sustainable economic development. This study aims to discuss the protection of Geographical Indications both in national and international laws, and analyze certain vital steps to efficiently utilizing Indonesia's GI as trade commodities. The paper will mainly discuss Geographical Indication legal protection and ways to utilize it for the country's economy. The study finds that the legal protection of GI in Indonesia is still considered weak and lacks in parties' active involvement in managing GI-based trade commodities and products. The research concluded that to strengthen GI protection in Indonesia, related party involvement and continuous monitoring and promoting are necessary to be done. Furthermore, the advice is to increase local community awareness by government and non-governmental organizations toward GI potential. It includes developing an efficient protection and management system that fully maximized each party's ability to execute its responsibility. KEYWORDS: Geographical Indications, Intellectual Property, Economic Development.